1998
DOI: 10.1002/(sici)1098-1004(1998)11:1<76::aid-humu12>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the 6‐pyruvoyl‐tetrahydropterin synthase gene in Chinese hyperphenylalaninemia caused by tetrahydrobiopterin synthesis deficiency

Abstract: Hyperphenylalaninemia (HPA) may be caused by deficiency of phenylalanine hydroxylase or tetrahydrobiopterin (BH4), the essential cofactor for the aromatic amino acid hydroxylases. 6-Pyruvoyl-tetrahydropterin synthase (PTPS) deficiency is a major cause of BH4 deficient HPA. In this study, seven single base mutations at nucleotides 73 (C>G), 155 (A>G), 166 (G>A), 209 (T>A), 259 (C>T), 286 (G>A), and 317 (C>T) on PTPS cDNA were detected in Chinese PTPS-deficient HPA by polymerase chain reaction and solid phase DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…14 In some cases, genomic DNA was extracted from blood samples, cultured fibroblasts or lymphoblasts by standard protocols. The DNA fragments for all patients as well as the normal controls were amplified by PCR followed by bidirectionally fluorescent sequencing on an ABI 377 or ABI 3730xl DNA analyzer (Life Technologies, Carlsbad, CA, USA) with BigDye chemistry (Life Technologies).…”
Section: Mutation Analysismentioning
confidence: 99%
“…14 In some cases, genomic DNA was extracted from blood samples, cultured fibroblasts or lymphoblasts by standard protocols. The DNA fragments for all patients as well as the normal controls were amplified by PCR followed by bidirectionally fluorescent sequencing on an ABI 377 or ABI 3730xl DNA analyzer (Life Technologies, Carlsbad, CA, USA) with BigDye chemistry (Life Technologies).…”
Section: Mutation Analysismentioning
confidence: 99%
“…The method for genomic DNA isolated from dried blood spot sample has been described previously (Hong et al 1999;Liu et al 1998). All 13 exons of the MUT gene, including coding and non-coding exons, and exon-intron boundary sequences were PCR-amplified and directly sequenced by thermocycle sequencing using the BigDye ® terminator 3.1 sequencing kit (Applied Biosystems, Foster City, CA, USA) following analysis by an ABI 3730XL DNA Analyzer (Applied Biosystems).…”
Section: Subjectsmentioning
confidence: 99%
“…The method for genomic DNA isolated from a dried blood spot collected on filter paper has been described elsewhere. [20][21] The whole coding region sequence and exon-intron boundary sequence of the MMACHC gene were PCR amplified using primer sets for exons 1, 2, 3 and 4a as described by Lerner-Ellis et al 7 For patients with only one mutation identified in the coding exons and flanking sequence, sequence analysis was extended into the 3¢-untranslated region (exons 4b, 5a and 5b in Lerner-Ellis et al 7 ). The four coding exons and exon-intron boundary sequence of the MMACHC gene were also sequenced in 70 anonymous Chinese controls.…”
Section: Mutation Analysismentioning
confidence: 99%